The phosphorylated trimeric SOSS1 complex and RNA polymerase II trigger liquid-liquid phase separation at double-strand breaks - Long, Qilin; Sebesta, Marek; Sedova, Katerina; Haluza, Vojtech; Alagia, Adele; Liu, Zhichao; Stefl, Richard; Gullerova, Monika (Cell reports, 2023)
Double-strand breaks (DSBs) are the most severe type of DNA damage. Previously, we demonstrated that RNA polymerase II (RNAPII) phosphorylated at the tyrosine 1 (Y1P) residue of its C-terminal domain (CTD) generates RNAs at DSBs. However, the regulation of transcription at DSBs remains enigmatic. Here, we show that the damage-activated tyrosine kinase c-Abl phosphorylates hSSB1, enabling its interaction with Y1P RNAPII at DSBs. Furthermore, the trimeric SOSS1 complex, consisting of hSSB1, INTS3, and c9orf80, binds to Y1P RNAPII in response to DNA damage in an R-loop-dependent manner. Specifically, hSSB1, as a part of the trimeric SOSS1 complex, exhibits a strong affinity for R-loops, even in the presence of replication protein A (RPA). Our in vitro and in vivo data reveal that the SOSS1 complex and RNAPII form dynamic liquid-like repair compartments at DSBs. Depletion of the SOSS1 complex impairs DNA repair, underscoring its biological role in the R-loop-dependent DNA damage response.
Keywords: DNA vazebné proteiny; oprava DNA; DNA Damage; hSSB1; phosphorylation; c-Abl kinase; phase-separation; DNA:RNA hybrids; DNA Repair; R-loops; SOSS1 complex; DNA damage; LLPS; poškození DNA; RNA-polymerasa II; DNA-Binding Proteins; RNA polymerase II; RNA Polymerase II; separace fází; CP: Molecular biology; Phase Separation